Environmental modelling, software and decision support state of the art and new perspectives - Jakeman, A. J. (Amsterdam ; Boston : Elsevier, 2008)
The complex and multidisciplinary nature of environmental problems requires that they are dealt with in an integrated manner. Modeling and software have become key instruments used to promote sustainability and improve environmental decision processes, especially through systematic integration of various knowledge and data and their ability to foster learning and help make predictions. This book presents the current state-of-the-art in environmental modeling and software and identifies the future challenges in the field. State-of-the-art in environmental modeling and software theory and practice for integrated assessment and management serves as a starting point for researchers. Identifies the areas of research and practice required for advancing the requisite knowledge base and tools, and their wider usage. Best practices of environmental modeling enables the reader to select appropriate software and gives the reader tools to integrate natural system dynamics with human dimensions.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Environmental sciences -- Computer simulation; Electronic books